Optimization of oligofructans production from sugarcane juice fermentation using Bacillus subtilis TISTR001 - Ninchan, Boontiwa; Noidee, Chanyanuch (Agriculture and Natural Resources, 2022)
Oligofructans are healthy prebiotic compounds linked by β-glycosidic fructose. They have received increasing attention due to their positive health effect. The objective of this research was the optimization of oligofructans fermentation conditions from sugarcane juice using Bacillus subtilis TISTR001 that produced fructose polymer enzyme as levansucrase. The cane juice was adjusted to pH 6.8 and supplemented with meat extract (3 g/L), peptone (5 g/L), (NH4)2SO4 (2 g/L), and MgSO4.7H2O (0.6 g/L). It was found that the oligofructans increased in proportion with the sugarcane juice concentration. The maximum juice concentration was 20 brix, with the highest content of oligofructans in the form of free fructose being 3.79% (w/v) with 0.29 g/g reducing sugar production yield and 0.045 g/L/h productivity. Additionally, 84 hr of fermentation at 30°C were the optimum conditions to produce the highest oligofructans content, which was confirmed by the complete use of the sugars content, sucrose and free fructose.